SWOT Analysis in Optimizing Human Capital in Fastco Recycle Household Waste Management in Genteng District - Elok Rosyidah; Firli Adri Ridhotama; Isti Fadah; Ni Made Widnyani; Dilla Cattleyana (International Publisher (YAPENBI), 2025)
This study aims to analyze the optimizationhuman capitalin household waste management through a SWOT analysis approach at Fastco Recycle Genteng, Banyuwangi Regency. The focus of the research is to identify the strengths, weaknesses, opportunities, and threats that affect the sustainability of the community-based waste management system. The approach used is descriptive qualitative with data collection through in-depth interviews, direct observation, and documentation studies of Fastco Recycle members, participating communities, and local stakeholders. The research instruments include interview guidelines, observation sheets, and a SWOT matrix (IFAS and EFAS) to analyze internal and external factors of the organization. The results show that Fastco Recycle Genteng has strong human capital with transformational leadership characteristics, a strong environmental commitment, and active collaboration with the community and academics. However, limitations in funding, formal training, and digital marketing skills remain obstacles. The SWOT analysis places Fastco Recycle in Quadrant I (Aggressive Strategy) with dominant internal strengths (X=+2.4) and significant external opportunities (Y=+1.3). These findings indicate that strengthening human capital through capacity building, innovation, and cross-sector collaboration are key to supporting a circular economy and realizing the vision of societyzero wastein Genteng District.